A kind of lining casting material of aluminum melting furnace without silicon ash and preparation method thereof
By eliminating the silica fume component in the castables of the aluminum melting furnace, preventing the introduction of SiO2, and constructing a high-purity silicon fume-free system, the problem of corundum nodule formation is solved, and the service life of the aluminum melting furnace and the performance of the material are improved.
Patent Information
- Application Number
- CN202411033743.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The prior art cannot fundamentally prevent the reaction of aluminum liquid and SiO2 to form corundum, resulting in a shortening of the service life of the melted aluminum furnace.
Silica fume-free castables are used to eliminate the silica fume component in the castables to prevent the introduction of free SiO2 and construct high-purity silicon fume-free aluminum melting furnace castables to prevent the formation of corundum nodules from the source.
It effectively reduces the generation of corundum nodules, extends the service life of the aluminum melting furnace, and maintains the material's high density, resistance to erosion by liquid aluminum, wear resistance and impact resistance.
Smart Images

Figure CN118771865B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory castables, and in particular relates to a silica ash-free aluminum melting furnace lining castable and a preparation method thereof. Background Art
[0002] Silica fume, also known as silica micropowder or ultrafine silica powder, is an ultrafine siliceous powder material with high fineness. It is mainly composed of silicon dioxide (SiO2), and the content can reach 75% to 96%. The particles of silica fume are very fine, more than 80% of the particles are less than 1 micron, the average particle size is between 0.1 and 0.3 microns, and it has a high specific surface area of 20 to 28 square meters / gram. These characteristics enable silica fume to significantly improve the mechanical properties of the material. In refractory castables, silica fume can improve the fluidity and construction performance of the castable, reduce water consumption, enhance the density of the lining material, improve the material's anti-permeability, and enhance the refractory performance; therefore, silica fume is a very important component in refractory castables.
[0003] Corundum nodules generally refer to the alumina-rich areas formed in the refractory materials of the lining of the aluminum alloy melting furnace (aluminum melting furnace), which will cause the lining materials to break and affect the normal use and life of the aluminum melting furnace. Studies have shown that the formation of corundum nodules is closely related to the use of silica fume in the furnace lining castable. The aluminum and other alloy elements in the aluminum melt in the molten pool react chemically with the main component SiO2 in the silica fume:
[0004] 4Al+3SiO2→3Si+2Al2O3,
[0005] 2Mg+SiO2→Si+2MgO,
[0006] MgO+Al2O3→MgO·Al2O3.
[0007] Among them, the corundum phase (Al2O3) is the main component of the corundum nodules, with a mass fraction of up to 94%. The corundum phase is initially formed on the surface of the furnace lining, but as the reaction proceeds, the replaced Si will increase the fluidity of the aluminum liquid in the molten pool. The aluminum liquid penetrates into the furnace lining material through capillary action or cracks and joints, further reducing SiO2, causing the corundum phase to spread into the furnace lining and combine with the material. The MgO·Al2O3 generated by the reaction, that is, magnesium-aluminum spinel, expands in volume during its formation, causing the surface of the furnace lining to peel off, which further aggravates the erosion process of the corundum nodules.
[0008] In the prior art, for example, CN109400188A discloses an anti-seepage castable for an aluminum melting furnace and a preparation method thereof, which uses low-porosity coke gemstone as the main raw material for the aluminum melting furnace lining. This method can only prevent high-temperature molten aluminum from penetrating the lining castable to a certain extent, but cannot completely prevent the aluminum liquid from chemically reacting with free SiO2 to form corundum nodules. CN117383912B discloses a non-stick aluminum castable and a preparation method thereof, which uses wollastonite powder as an anti-aluminum liquid corrosion agent. However, this can only reduce the high-temperature shrinkage and cracking of the furnace lining material, and due to the addition of wollastonite powder, the above-mentioned corundum nodule formation reaction is easier to proceed, so it actually cannot achieve the effect of improving the formation of corundum nodules, and cannot fundamentally prevent the aluminum liquid from reacting with SiO2 to form corundum nodules.
[0009] Therefore, developing new refractory materials to prevent the formation of corundum nodules from the source, while ensuring that the materials have high density, resistance to aluminum liquid corrosion, wear resistance and impact resistance, is the key to improving the service life of aluminum melting furnaces. Summary of the invention
[0010] In view of the above-mentioned reason that SiO2 in the aluminum melting furnace lining material reacts with aluminum and other alloy elements in the aluminum melt to form corundum nodules, the present invention provides a silicon ash-free aluminum melting furnace lining castable and a preparation method, and for the first time proposes not to add silicon ash to the raw materials to prevent the introduction of free SiO2, to construct a high-purity silicon ash-free aluminum melting furnace castable, and to prevent the formation of corundum nodules from the root. The specific technical scheme is as follows:
[0011] Firstly, the present invention provides a silica ash-free aluminum melting furnace lining castable, which is composed of a silica ash-free main material, an organic fiber material, a water reducer and an aluminum-free additive; wherein the components of the silica ash-free main material are composed of the following raw materials in percentage by mass: 45-55% of plate-shaped corundum powder, 30-40% of white corundum powder, 4-6% of alumina powder, and 5-10% of a binder; the organic fiber material is a low-melting-point polypropylene fiber, and its usage is 0.1-0.3% of the total mass of the silica ash-free main material; the water reducer is a polycarboxylate water reducer, and its usage is 0.05-0.15% of the total mass of the silica ash-free main material; the aluminum-free additive is a two-component composite additive of BaSO4 and CA6, and its usage is 3-7% of the total mass of the silica ash-free main material.
[0012] The aforementioned silica ash-free aluminum melting furnace lining castable, the mass ratio of BaSO4 to CA6 in the non-aluminum-sticking additive is 2-4:1-3.
[0013] Preferably, in the aforementioned silica ash-free aluminum melting furnace lining castable, the mass ratio of BaSO4 to CA6 in the non-aluminum-sticking additive is 2.5:1.5.
[0014] The aforementioned silica ash-free aluminum melting furnace lining castable, the polycarboxylate water reducer includes an unmodified SD-water reducer and a silane-modified SD-water reducer, and the silane modifier used in the silane-modified SD-water reducer is γ-(methacryloyloxy)propyltrimethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560) or γ-methacryloyloxypropyltrimethoxysilane (KH570).
[0015] Preferably, the preparation method of the silane-modified SD-water reducer is: using ammonium persulfate as an initiator and mercaptopropionic acid as a chain transfer agent, acrylic acid, isoprenyl polyoxyethylene ether and a silane modifier are mixed in a mass ratio of 1:1:1, copolymerized in a water bath at 80°C to obtain a copolymer, and then adjusting the pH to 7.
[0016] The aforementioned silica ash-free aluminum melting furnace lining castable, the melting point of the low-melting-point polypropylene fiber is 90-100°C.
[0017] The aforementioned silica ash-free aluminum melting furnace lining castable, in the silica ash-free main material, the particle size of the plate-shaped corundum powder is 0.001-3mm, the particle size of the white corundum powder is 3-10mm, the particle size of the alumina powder is less than 0.045mm, and the binder is 70 calcium aluminate refractory cement.
[0018] Secondly, the present invention provides a method for preparing a lining of a silicon ash-free aluminum melting furnace, which is prepared by using the aforementioned castable; specifically comprising the following steps:
[0019] 1) Casting material preparation: Weigh the components of the casting material according to the above mass percentages, first mix the plate-shaped corundum powder, white corundum powder, binder, alumina powder, water reducer and non-stick aluminum additive, then add an appropriate amount of water to adjust the material to have appropriate fluidity, then add the fiber material, and continue stirring to obtain the casting material;
[0020] 2) Casting material construction: The prepared casting material is poured into the prefabricated mold in the aluminum melting furnace through the casting equipment while being stirred, in preparation for drying and curing;
[0021] 3) Drying and curing: After the construction of the castable is completed, the castable injected into the mold is baked to dissipate the moisture inside until it is completely dry;
[0022] 4) Demolding: After the castable in the mold is completely dry, remove the mold to obtain the aluminum melting furnace lining.
[0023] As a preferred technical solution, in step 1), the castable is prepared: after adding the fiber material, the initial stirring speed is 20-100 rpm, stirring for 5-10 minutes to gradually disperse the fibers; then the stirring speed is gradually increased to 100-300 rpm, stirring for 10-15 minutes, until the castable reaches the required uniformity and fluidity; finally, the stirring speed is maintained at 200-300 rpm to ensure that the fibers do not clump and are evenly dispersed; and the stirring direction remains unchanged after adding the fiber material.
[0024] As a preferred technical solution, in step 3), the drying and curing process is:
[0025] Heating: First, heat to 90℃ at a rate of 2℃ / min and keep warm for 30min; then heat to 95℃ at a rate of 1℃ / min and keep warm for 3h; then heat to 99℃ at a rate of 0.5℃ / min and keep warm for 2h;
[0026] Cooling: Then cool to 95℃ at a rate of 0.5℃ / min and keep warm for 30min; then cool to 90℃ at a rate of 1℃ / min and keep warm for 2h; finally cool to room temperature at a rate of 3℃ / min and demould.
[0027] Beneficial effects of the present invention:
[0028] 1) Based on the formation mechanism of corundum nodules, the present invention removes silica fume from the castable, thereby blocking the possibility of corundum nodules from the castable matrix part; and improves the purity of the castable matrix part. Except for the Si-based compounds in the composition of the raw materials themselves, no additional Si-containing compounds are introduced, whether in the form of oxides or mullite, thereby preventing the introduction of free SiO2 from the source, constructing a high-purity silica fume-free aluminum melting furnace castable, reducing the generation of corundum nodules from the root, improving the corundum nodule problem of the aluminum melting furnace, and increasing the service life of the aluminum melting furnace.
[0029] 2) The present invention improves the composition and particle size distribution of the main raw materials to ensure the impact resistance of the refractory material without silica fume and the controllability of the stirring and pouring of the material; at the same time, the particle size distribution of the small-particle plate-shaped corundum is simplified to facilitate actual production operations; the SD-water reducer used in the present invention can not only ensure the adhesion and fluidity of the castable without silica fume, but also make the material fluffy and conducive to agglomeration for easy pouring during stirring, and will not produce backflow, thereby ensuring the mechanical strength of the lining material at high temperature; the low-melting-point polypropylene fiber used in the present invention can not only speed up the baking process, but also control the baking temperature within 100°C, thereby preventing the lining from loosening and cracking caused by water evaporation and expansion, and even explosion accidents, thereby improving the lining preparation efficiency and ensuring construction safety and product quality.
[0030] 3) The present invention uses a two-component non-stick aluminum additive composed of BaSO4 and CA6. BaSO4 and CA6 can work together to form a physical and chemical double barrier to ensure the stability of the physical and chemical properties of the lining material under the silica ash-free system at high temperatures. Among them, BaSO4 has a high density and is not easily wetted by aluminum liquid. It can form a physical barrier to reduce the direct contact between aluminum liquid and the refractory matrix, thereby reducing the erosion of aluminum liquid on the refractory material, while CA6 has excellent chemical stability at high temperatures, which can isolate and protect the stability of the alloy elements in the material in the high temperature and aluminum liquid environment, and prevent the chemical structure of the material from being destroyed; the combination of the two ensures that the prepared lining material has an inclusive expansion range, can well cope with temperature fluctuations in the molten pool, ensure that the lining material maintains stability under repeated thermal cycles, reduce cracks caused by thermal stress, and improve the thermal stability of the silica ash-free system castable. In the present invention, the composite mass ratio of BaSO4 and CA6 in the two-component non-stick aluminum additive is controlled to be 2-4:1-3, so as to ensure the bonding strength of the interface between the two; at the same time, CA6, as a high-temperature stable phase, helps to form a stable crystalline structure in the castable and establish a high-strength mechanical support system, while the addition of BaSO4 can help to fill the tiny gaps in the castable, reduce the number and size of pores, reduce the porosity of the lining material, and improve the chemical corrosion resistance of the castable.
[0031] 4) In the preparation method of the present invention, the amount of low-melting-point polypropylene fiber added is controlled to be 0.1-0.3% of the total mass of the main material without silica fume, which accelerates the loss of water during the baking process, while not affecting the self-flowability of the castable and the mechanical properties of the lining. In addition, the stirring speed and stirring direction are controlled during the preparation process to ensure that the fiber can be evenly dispersed in the castable and maintain its structural integrity. At the same time, the drying temperature is controlled, and the temperature is gradually increased, which helps the polypropylene fiber to gradually melt and quickly discharge the water inside the material; then the temperature is gradually reduced, so that the polypropylene fiber is gradually fully consolidated with the components of the casting material, and the cooling speed is avoided too fast, and the porous structure generated in the hardened polypropylene fiber increases the porosity of the lining material. And the gradual increase and decrease of the temperature can avoid thermal stress caused by rapid temperature changes, reduce thermal shock and thermal fatigue, avoid cracks on the surface or inside of the material, ensure that the lining material maintains its structural integrity during the entire drying process, and help to extend the service life of the material.
[0032] In general, the present invention proposes for the first time to prevent the introduction of free SiO2 by removing the silica ash component in the base material of the aluminum melting furnace lining, and to construct a high-purity silica ash-free aluminum melting furnace castable, thereby preventing the generation of corundum nodules from the root; at the same time, the composition and particle size distribution of the main raw materials are improved to ensure the impact resistance of the refractory material without silica ash and the controllability of the stirring and pouring of the material; through the prepared composite water reducing agent, the bonding and fluidity of the castable without silica ash are ensured to facilitate pouring, and the mechanical strength of the lining material at high temperature is ensured; by adopting an appropriate amount of low-melting-point polypropylene fiber, the baking process is accelerated to ensure the quality of the lining; and through the synergistic effect of BaSO4 and CA6, the overall performance of the castable without silica ash system is ensured, especially in terms of resistance to aluminum liquid corrosion, structural stability, high temperature performance and slag resistance. The present invention makes up for the potential weaknesses of the silica ash-free system through the optimization of the formula, and reduces the generation of corundum nodules from the root, improves the corundum nodule problem of the aluminum melting furnace, and increases the service life of the aluminum melting furnace. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a real picture of the lining of the aluminum melting furnace without silicon ash prepared by the present invention;
[0034] Figure 2 (a) is a re-burning line change diagram of the silicon ash-free aluminum melting furnace lining material prepared by the present invention;
[0035] Figure 2 (b) is a graph showing the reburning line changes of the lining material of the aluminum melting furnace containing silicon ash;
[0036] Figure 3 A schematic diagram of the structure of a test block with grooves prepared in the present invention;
[0037] Figure 4 (a) is the anti-infiltration test result of the aluminum alloy lining of the aluminum melting furnace without silicon ash prepared by the present invention;
[0038] Figure 4 (b) is the anti-infiltration test result of aluminum alloy lining in aluminum melting furnace containing silicon ash;
[0039] Figure 5 (a) is the salt-alkali corrosion test result of the lining of the silicon ash-free aluminum melting furnace prepared by the present invention;
[0040] Figure 5 (b) is the result of salt-alkali corrosion test on the lining of aluminum melting furnace containing silicon ash;
[0041] Figure 6 (a) is a silicon ash-free aluminum melting furnace lining prepared by using low melting point polypropylene fiber of the present invention;
[0042] Figure 6 (b) is a comparative lining of an aluminum melting furnace made of ordinary polypropylene fiber;
[0043] Figure 7 (a) is the TG curve of the silicon ash-free aluminum melting furnace lining 1 prepared by the present invention;
[0044] Figure 7 (b) is the heating rate curve of the lining 1 of the silicon ash-free aluminum melting furnace prepared by the present invention;
[0045] Figure 8 These are the anti-wetting test results of the aluminum alloy lining of the aluminum melting furnace prepared by the present invention. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described clearly and completely in combination with the embodiments below. The raw material components involved in the embodiments are all purchased from the market, and those without purity are all industrial or reagent grade.
[0047] Example 1
[0048] This embodiment is to prepare a lining material for a non-silica ash aluminum melting furnace. According to the mass percentage, 50% of plate-shaped corundum powder (particle size 0.5mm), 35% of white corundum powder (particle size 5mm), 8% of 70 calcium aluminate refractory cement, and 7% of alumina powder (particle size 0.05mm) are weighed as the main materials of the furnace lining castable; then 0.2% of the total weight of the main material is low-melting point polypropylene fiber (purchased from ELKEM, model DRY-SIL, melting point 90-100°C), 0.1% of the total weight of the main material is unmodified SD-water reducer, and 5% of the total weight of the main material is non-stick aluminum additive for use; wherein, BaSO4 in the non-stick aluminum additive accounts for 3% of the total weight of the main material, and CA6 (calcium hexaaluminate) accounts for 2% of the total weight of the main material.
[0049] The specific preparation process of the aluminum melting furnace lining is as follows:
[0050] 1) Casting material preparation: First, weigh the castable components according to the above mass percentages, mix the plate-shaped corundum powder, white corundum powder, 70 calcium aluminate refractory cement, alumina powder, unmodified SD-water reducer, BaSO4 and CA6, stir to make the materials uniform, add an appropriate amount of water (3.50% of the total weight of the dry material), adjust to the material has a suitable fluidity, then add polypropylene fiber, continue to stir, and keep the stirring direction unchanged to obtain the casting material for use. After adding the fiber material, the initial stirring speed is 50rpm, stir for 10 minutes to gradually disperse the fiber; then gradually increase the stirring speed to 200rpm, stir for 15 minutes, until the castable reaches the required uniformity and fluidity; finally, keep the stirring speed at 200rpm to ensure that the fiber does not clump and is evenly dispersed.
[0051] 2) Casting material construction: The prepared casting material is poured into the prefabricated mold in the aluminum melting furnace (the mold is prefabricated according to specific needs) through the casting equipment while stirring, in preparation for drying and curing. During the casting process, the stirring speed is always maintained at 200rpm, and the stirring direction remains unchanged.
[0052] 3) Drying and curing: After the casting construction is completed, the casting injected into the mold is baked to dissipate the moisture inside until it is completely dry; the drying and curing process is as follows:
[0053] Heating: First, heat to 90℃ at a rate of 2℃ / min and keep warm for 30min; then heat to 95℃ at a rate of 1℃ / min and keep warm for 3h; then heat to 99℃ at a rate of 0.5℃ / min and keep warm for 2h;
[0054] Cooling: Then cool to 95℃ at a rate of 0.5℃ / min and keep warm for 30min; then cool to 90℃ at a rate of 1℃ / min and keep warm for 2h; finally cool to room temperature at a rate of 3℃ / min and demould.
[0055] 4) Demolding: After the castable in the mold is completely dried, the mold is removed to obtain the silica-ash-free aluminum melting furnace lining material 1 (referred to as lining 1). Figure 1 shown.
[0056] Example 2
[0057] This example is to investigate the mechanical properties and corundum nodule generation of the silica-free lining material prepared in Example 1. The investigation angles of this example include mechanical strength test, anti-infiltration test, salt-alkali corrosion resistance test, and analysis of the thermal expansion and reburning line changes of the lining material. The details are as follows:
[0058] In order to verify the influence of silica ash on the mechanical properties of the lining material and the generation of corundum nodules, this example is based on the formula of the lining of the aluminum melting furnace without silica ash in Example 1, and a lining of the aluminum melting furnace with silica ash is prepared as a comparative lining. The lining of the aluminum melting furnace with silica ash only adds silica ash to the main component of the lining, and the other components and amounts are consistent with Example 1, and the preparation process and parameters are also the same as Example 1. The main materials of the lining of the aluminum melting furnace with silica ash are calculated by mass percentage: 50% of plate-shaped corundum powder (particle size 0.5mm), 35% of white corundum powder (particle size 5mm), 70% of calcium aluminate refractory cement, 5% of alumina powder (particle size 0.05mm), and 3% of silica ash. The prepared lining material of the aluminum melting furnace with silica ash is recorded as comparative lining 1.
[0059] 1) Mechanical strength test
[0060] In this embodiment, the mechanical properties tested include the flexural and compressive strength, density and linear change rate after sintering at 110℃ / 800℃ / 1200℃ / 1500℃, that is, the silica ash-free aluminum melting furnace lining 1 and the comparison lining 1 are heated to 110℃, 800℃, 1200℃, and 1500℃ respectively and then cooled to room temperature to test their flexural and compressive capabilities and examine their heating permanent linear change rate, and their density is tested respectively.
[0061] First, the silica ash-free castable prepared in Example 1 and the silica ash castable in this example were respectively injected into a prefabricated triple mold (51*51*228mm), and the construction and maintenance methods were the same as in Example 1. Mechanical strength test specimens of the silica ash-free aluminum melting furnace lining 1 (lining 1) and the silica ash-containing aluminum melting furnace lining (comparative lining 1) were prepared respectively, and then the test items were carried out. Among them, the flexural and compressive test methods refer to ASTM C 133-1997 (2003), the density test method refers to GB / T 2997, and the heating permanent linear change rate test refers to GB / T 5988-2022. The test results are shown in Table 1:
[0062] Table 1. Mechanical properties test results of materials with and without silica fume lining
[0063]
[0064] It can be seen from the results in Table 1 that the silica fume-free lining material of the present invention has a similar density to the silica fume lining material, but has significantly improved flexural strength and compressive strength, and the linear change rate is also significantly improved, indicating that the silica fume-free castable of the present invention has a large bulk density, higher strength, and better volume stability.
[0065] 2) Analysis of thermal expansion and reburning line changes
[0066] First, the silica fume-free castable prepared in Example 1 and the silica fume castable in this example are respectively injected into prefabricated molds to make cylinders with dimensions of d=50 mm and h=50 mm. The construction and maintenance methods are the same as those in Example 1 to obtain thermal expansion and refiring line change analysis specimens. The demolded specimens are then fired at 200°C (deep water removal) and placed in a thermal expansion testing machine for thermal expansion testing and refiring line change analysis.
[0067] The specific experimental process is: place the specimen in a thermal expansion tester, heat it to 1500 degrees at a heating rate of 2 degrees per minute, cool it to room temperature at a cooling rate of 3 degrees per minute, and then re-burn it under the above conditions to measure the changes in the re-burning line. The experimental results are as follows Figure 2As shown in (a) and (b), the test results show that the silica fume-free castable prepared by the present invention has a smaller rate of change of thermal expansion line than the comparative lining material containing silica fume, the curve expands steadily, and the original volume can be basically restored by re-firing, without shrinkage or glass phase generation, and has good thermal shock resistance.
[0068] 3) Anti-infiltration test
[0069] The silica fume-free castable prepared in Example 1 and the silica fume castable in this example were respectively poured into a prefabricated mold to make a test block with a groove. The size of the test block is as follows: Figure 3 The anti-infiltration test process is as follows:
[0070] Put the test block with grooves into an oxidizing atmosphere furnace, heat it to 815℃ (heating rate within 300℃ / h), open the furnace, put 7075 aluminum alloy into the groove of the test block (the liquid level is 3mm from the top of the test block), and keep it at 815℃ for 72 hours. In the first three hours, stir the aluminum liquid with a rake every half an hour to eliminate the protective film between the refractory material and the aluminum liquid. The rake can be made of stainless steel coated with graphite, boron nitride or other protective layers. When the insulation is close to 72 hours, remove the oxide on the metal surface in advance, pour out the metal liquid for analysis, clean the surface of the test block immediately with a ceramic fiber blanket, and observe the non-stick aluminum performance and cleaning difficulty, then place the test block in the air to cool down and observe the metal erosion and penetration.
[0071] The results are as follows Figure 4 As shown in (a) and (b), the anti-infiltration test results show that the silica fume-free castable of the present invention does not show the phenomenon of aluminum liquid infiltration, while the silica fume-containing castable has obvious corundum nodule production phenomenon. This proves that the free silica fume in the lining material does have an important influence on the anti-infiltration performance of the lining and the formation of corundum nodules. It also proves that the silica fume-free castable of the present invention has good anti-infiltration performance and can curb the formation of corundum nodules from the source.
[0072] 4) Salt and alkali corrosion resistance test
[0073] The test block preparation steps are the same as the anti-infiltration test. The salt-alkali corrosion test process is as follows: put the test block with grooves into an oxidizing atmosphere furnace, heat it to 815 degrees (heating rate within 300℃ / h), open the furnace, put 50g of salt-alkali reagent (slag-removing agent, purchased from Jiangsu Xuzhou Siyuan Aluminum Group) into the groove, and keep it at 1150 degrees for 5 hours. Then place the test block in the air to cool down, and observe the erosion and penetration. The results are as follows Figure 5 As shown in (a) and (b), the test results show that even if 50 times the dosage of slag remover is added, the salt-alkali corrosion of the silica fume-free castable prepared by the present invention is very small, while the salt-alkali corrosion of the silica fume-containing castable as a comparison is more obvious. It can be seen that the silica fume-free castable of the present invention has a good salt-alkali resistance effect.
[0074] Various tests have shown that the silica fume-free lining material of the present invention has a matrix part that does not contain free SiO2, a pure system, and has the characteristic of not sticking to aluminum, which can basically eliminate the occurrence of corundum nodules; at the same time, it has low porosity, high mechanical strength, good thermal shock resistance, and good salt-alkali resistance, and is more suitable for high-purity aluminum smelting, and has good practical value and market promotion value.
[0075] Example 3
[0076] This example investigates the effects of the type and amount of polypropylene fiber on the baking moisture loss effect of the lining castable and the performance of the prepared lining.
[0077] This embodiment is based on the embodiment 1, and the types and amounts of polypropylene fibers in the lining castables involved in the investigation are shown in Table 2, wherein ordinary polypropylene fibers were purchased from Shandong Hongyao Copper Materials Co., Ltd.
[0078] Table 2. Type and amount of polypropylene fiber in the lining of each aluminum melting furnace
[0079]
[0080] In the table, lining materials 2-5 and comparative lining material 2 differ from Example 1 in the type and amount of organic fiber materials used, while the other components and amounts are consistent with Example 1; wherein, the preparation process and parameters of lining materials 2-5 are also the same as those of Example 1. The preparation process of comparative lining material 2 differs from Example 1 in the drying and curing temperature, while the rest are the same as those of Example 1. The drying and curing process of comparative lining material 2 is as follows:
[0081] Heating: First, heat to 100°C at a rate of 3°C / min and keep warm for 30 minutes; then heat to 105°C at a rate of 1°C / min and keep warm for 3 hours; then heat to 110°C at a rate of 0.5°C / min and keep warm for 2 hours;
[0082] Cooling: Then cool to 105℃ at a rate of 0.5℃ / min and keep warm for 30min; then cool to 100℃ at a rate of 1℃ / min and keep warm for 2h; finally cool to room temperature at a rate of 3℃ / min and demould.
[0083] In this embodiment, the thermal weight loss and fluidity of the lining castable are investigated, and the castable is heated at 300°C for 24 hours to investigate the drying condition and whether cracks are generated. The details are as follows:
[0084] Fluidity test, referring to the standard GB / T4513.4, each lining castable is stirred to a suitable viscosity according to the standard water addition amount (3.50% of the total weight of dry material), injected into the fluidity test mold and vibrated, then demolded and naturally vibrated for 30s, so that each lining castable can flow freely and flatten, and then the diameter size (mm) of the vibrated flattened area of the castable is measured. Then each castable is injected into a prefabricated mold to make a 50*50mm sample block. The construction and maintenance methods are the same as those in Example 1. After demolding, it is placed in an oven and baked at 400℃ for 24 hours. The drying condition of the lining and the cracks of the lining are observed. The results are shown in Table 3 and Figure 6 As shown in (a) and (b).
[0085] Then, each casting material was injected into a prefabricated mold to make a 10*10 mm sample. The construction and maintenance methods were the same as those in Example 1 to obtain a thermogravimetric analysis specimen. The demoulded specimen was placed in a thermogravimetric scale and the weight loss curve was recorded. The results are as follows: Figure 7 As shown in (a) and (b).
[0086] Table 3. Effect of polypropylene fiber type and dosage on lining casting molding
[0087] Aluminum melting furnace lining Flowability(mm) Lining dryness Lining cracks Lining 2 205 Partial drying No cracks Lining 3 202.5 Completely dry No cracks Lining 1 195 Completely dry No cracks Lining 4 185 Completely dry No cracks Lining 5 170.5 Completely dry No cracks Contrast lining 2 190 Not completely dry Micro cracks
[0088] It can be seen from the test results in Table 3 that the amount of low-melting-point polypropylene fiber has a significant effect on the fluidity of the lining castable, and if the amount of low-melting-point polypropylene fiber is too low, it is difficult to completely dry it in a short time, and if the amount is too high, the castable has poor fluidity, which is not conducive to pouring construction. Taking all factors into consideration, it is more appropriate to control the amount of low-melting-point polypropylene fiber to 0.1-0.3% of the total mass of the main material without silica fume. The use of ordinary polypropylene fiber has no obvious effect on the fluidity of the lining castable, but has a greater impact on the drying situation, and the prepared lining material has cracks. This is because the use of ordinary polypropylene fiber cannot fully dissipate the moisture during the drying and curing stage, and the internal moisture is relatively high. Under high-temperature baking, the moisture vaporizes and expands in volume, causing the lining material to crack and produce fine lines.
[0089] like Figure 7 The thermogravimetric analysis results shown in (a) and (b) indicate that, compared with the comparative lining 2 using ordinary polypropylene fibers, the silica fume-free castable of the present invention has a faster water loss rate in the low temperature zone (<200°C), and is substantially completely baked after 400°C, and can provide a suitable baking curve, further demonstrating that the use of low-melting-point polypropylene fibers can produce a porous structure to increase the porosity of the lining material, thereby avoiding thermal stress caused by rapid temperature changes, reducing thermal shock and thermal fatigue, and avoiding cracks on the surface or inside of the material, thereby ensuring that the lining material maintains its structural integrity during the entire drying process, and thus helping to extend the service life of the material.
[0090] Example 4
[0091] This example is based on Example 1 to investigate the effect of the type of water reducer on the lining castable. In each lining castable investigated, except for the type of water reducer, which is different from that in Example 1, the other components, dosage, preparation process and parameters are the same as those in Example 1. In addition to the type and dosage of the water reducer, the lining castables investigated are shown in Table 4.
[0092] Table 4. Type and dosage of water reducing agent in the lining of each aluminum melting furnace
[0093]
[0094] Among them, the KH550 silane-modified SD-water reducer, KH560 silane-modified SD-water reducer, and KH570 silane-modified SD-water reducer are all prepared by aqueous solution free radical polymerization. Specifically, using ammonium persulfate as an initiator and mercaptopropionic acid as a chain transfer agent, acrylic acid, isoprene polyoxyethylene ether and silane modifier KH550, KH560 or KH570 are mixed in a mass ratio of 1:1:1, and copolymerized in a water bath at 80°C to obtain a random copolymer. In a four-necked flask with a thermometer and a stirrer, add isoprene polyoxyethylene ether monomer with a relative molecular weight of 2400, ammonium persulfate, part of acrylic acid and a certain amount of deionized water, and after heating to 80°C, add acrylic acid solution and a mixed solution of hydrogen peroxide and mercaptopropionic acid, respectively, and the dropping time is 1.5 and 2h, respectively. After the reactants were completely added, the temperature was kept for 30 minutes, and then the synthetic product was neutralized with 25% NaOH solution to pH = 7, and then the reaction product was dialyzed with a semipermeable membrane (MD44-7) before use.
[0095] The investigation method in this embodiment uses the fluidity and water return of each prepared castable and the mechanical strength of the prepared lining as evaluation indicators. The fluidity test refers to Example 3; the mechanical strength test refers to Example 2, and the test results are shown in Table 5.
[0096] Table 5. Effect of water reducing agent on lining castable and lining mechanical strength
[0097]
[0098] It can be seen from the test results in the table that the SD series water reducer used in the present invention can make the lining castable have better fluidity, and the silane-modified SD-water reducer can further enhance the fluidity of the material, which is beneficial to the casting construction; most importantly, the castable prepared by the SD series water reducer used in the present invention does not have the backflow phenomenon, and the mechanical strength is significantly improved, which comprehensively improves the performance of the lining material.
[0099] Example 5
[0100] This example is based on Example 1 to investigate the effects of the type and amount of the non-stick aluminum additive on the density, thermal shock resistance, anti-wetting and occurrence of corundum nodules of the prepared lining material. Except for the type and amount of the non-stick aluminum additive, the other components and amounts of the lining castables involved in the investigation are the same as those in Example 1, and the preparation process and parameters are also the same as those in Example 1. Except for the type and amount of the water reducer, the lining castables involved in the investigation are shown in Table 6.
[0101] Table 6. Types and dosages of non-stick aluminum additives in the lining of each aluminum melting furnace
[0102] No aluminum additives Lining 9 Lining 10 Lining 11 Lining 1 Lining 12 Lining 13 Contrast lining 6 Contrast lining 7 BaSO4 1.5 2 2.5 3 4 4.5 3 -- CA6 0.5 1 1.5 2 3 3.5 -- 2
[0103] This example uses the density of the lining material at 1500°C, the presence of cracks after thermal shock, the aluminum alloy infiltration and the corundum nodule formation as the inspection indicators. The density detection method and the preparation method of the anti-infiltration test specimen are both referred to Example 2. The details are as follows:
[0104] The test block with grooves prepared by the method of Example 2 was placed in an oxidizing atmosphere furnace, heated to 1500°C (heating rate within 300°C / h), the furnace was opened, 7075 aluminum alloy was placed in the groove of the test block (the liquid level was 3mm from the top of the test block), and kept at 1500°C for 24 hours. Then the temperature was lowered (cooling rate within 300°C / h) to room temperature, and the temperature was repeatedly raised to 1500°C, kept for 24 hours, and then cooled, and repeated 15 times. When the last heat preservation reached 24 hours, the oxide on the metal surface was removed, the metal liquid was poured out for component analysis, the surface of the test block was immediately cleaned with a ceramic fiber blanket, and the non-stick aluminum performance and cleaning difficulty were observed, and then the test block was placed in the air to cool down, and the metal corrosion and penetration were observed.
[0105] Results Table 7 and Figure 8 As shown, the anti-infiltration test results are shown.
[0106] Table 7. Effect of type and amount of non-stick aluminum additives on lining materials
[0107] Lining material <![CDATA[Density (g / cm 3 )]]> Difficulty of cleaning Aluminum liquid infiltration Corundum tumor formation Crack situation Lining 9 2.85 Difficult to clean Aluminum liquid infiltration is obvious Corundum tumor formation Micro cracks Lining 10 2.91 Easy to clean Aluminum liquid infiltration is not obvious The corundum tumor is not obvious No cracks Lining 11 3.01 Easy to clean Aluminum liquid infiltration is not obvious The corundum tumor is not obvious No cracks Lining 1 3.08 Easy to clean Aluminum liquid infiltration is not obvious The corundum tumor is not obvious No cracks Lining 12 3.13 Easy to clean Aluminum liquid infiltration is not obvious The corundum tumor is not obvious No cracks Lining 13 3.19 Easy to clean Aluminum liquid infiltration is not obvious Corundum tumor formation Micro cracks Contrast lining 6 2.93 Difficult to clean Aluminum liquid infiltration is obvious Obvious corundum tumor Micro cracks Contrast lining 7 2.76 Difficult to clean Aluminum liquid infiltration is obvious Obvious corundum tumor Micro cracks
[0108] The results of this embodiment show that within a certain dosage range, the combination of BaSO4 and CA6 as a non-stick aluminum additive can effectively improve the density and anti-infiltration and thermal shock resistance of the lining material, and the effect is significant as the dosage of the non-stick aluminum additive increases; but too low an amount of the non-stick aluminum additive cannot protect the furnace lining material well, the lining material has a low density, and the anti-infiltration and thermal shock resistance effects are not good; and due to the different thermal expansion coefficients of BaSO4 and CA6, excessive dosage of the two affects the bonding strength of the interface between the two, and cracks are easily generated during the thermal shock process, leading to the formation of corundum nodules.
[0109] Example 6
[0110] This example is based on Example 1 to investigate the effect of the preparation method on the prepared lining material. This example mainly investigates the effect of temperature control in the drying and curing process on the water loss of the lining material and the effect of the lining product. The specific investigation method is mainly completed through different drying experiments. Except for the drying process, the components and dosage of the castables and other processes and parameters of each experiment are the same as those in Example 1. The drying procedures in each experiment are as follows:
[0111] According to Example 3, a 10*10 mm sample was made, and the construction and maintenance methods were the same as in Example 1. The sample obtained was subjected to the following experiment:
[0112] Experiment 1: Same as Example 1. Heating: First, heat to 90℃ at a rate of 2℃ / min, keep warm for 30min; then heat to 95℃ at a rate of 1℃ / min, keep warm for 3h; then heat to 99℃ at a rate of 0.5℃ / min, keep warm for 2h; Cooling: Then cool to 95℃ at a rate of 0.5℃ / min, keep warm for 30min; then cool to 90℃ at a rate of 1℃ / min, keep warm for 2h; finally cool to room temperature at a rate of 3℃ / min, demould. Then place in an oven, bake at 200℃ for 24 hours, observe the dryness of the lining surface; continue baking, record the complete drying time of the lining and observe the cracks of the lining.
[0113] Experiment 2: Raise the temperature to 90℃ at a rate of 2℃ / min, keep warm for 30min; then raise the temperature to 95℃ at a rate of 2℃ / min, keep warm for 3h; then raise the temperature to 99℃ at a rate of 2℃ / min, keep warm for 2h; cool down: then cool down to 96℃ at a rate of 3℃ / min, keep warm for 30min; then cool down to 90℃ at a rate of 3℃ / min, keep warm for 2h; finally cool down to room temperature at a rate of 3℃ / min, demould. Then place in the oven, bake at 200℃ for 24 hours, observe the dryness of the lining surface; continue baking, record the complete drying time of the lining and observe the cracks of the lining.
[0114] Experiment 3: Heat to 90℃ at a rate of 2℃ / min and dry at a constant temperature for 8h, then cool to room temperature at a rate of 3℃ / min. Then place in an oven and bake at 200℃ for 24 hours, observe the dryness of the lining surface; continue baking, record the time for the lining to be completely dry, and observe the cracks in the lining.
[0115] Experiment 4: Heat to 99℃ at a rate of 2℃ / min and dry at a constant temperature for 8h, then cool to room temperature at a rate of 3℃ / min. Then place in an oven and bake at 200℃ for 24 hours, observe the dryness of the lining surface; continue baking, record the time for the lining to be completely dry, and observe the cracks in the lining.
[0116] The drying conditions of each lining were observed, as well as whether there were cracks in the lining. The results are shown in Table 8.
[0117] Table 8. Effect of temperature control in drying and curing process on lining materials
[0118] Aluminum melting furnace lining Lining surface drying condition within 24 hours of baking Lining material complete drying time Cracks in lining material Experiment 1 Completely dry 24h No cracks Experiment 2 Completely dry 24h There are cracks Experiment 3 Not completely dried 38h No cracks Experiment 4 Not completely dried 33h There are cracks
[0119] It can be seen from the experimental results in Table 8 that staged temperature rise and fall helps to disperse the water in the lining casting material and accelerate the drying of the lining; and carefully controlling the speed of temperature rise and fall during the temperature rise and fall process helps to effectively prevent the occurrence of cracks in the lining material. This is because if the water in the material is not completely discharged during the curing stage, the water will remain in the material. As the temperature rises, the material will crack due to the effect of vapor pressure.
[0120] In general, various tests have shown that the product of the present invention is developed based on high-purity corundum, the matrix part does not contain free SiO2, the system is pure, and has the characteristic of not sticking to aluminum, which can basically eliminate the occurrence of corundum tumors; at the same time, the lining prepared by the present invention has low porosity and high mechanical strength, and is more suitable for high-purity aluminum smelting.
[0121] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the implementation mode, it does not include only one technical solution. This narrative mode of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A silicon ash-free aluminum melting furnace lining castable, characterized in that: The castable is composed of a silica-free main material, an organic fiber material, a water reducing agent and an aluminum-free additive; The components of the silica-free main material are composed of the following raw materials by mass percentage: Platy corundum powder 45~55%, White corundum powder 30-40%, Alumina powder 4-6%, Binder 5-10%; The organic fiber material is low melting point polypropylene fiber, and its usage is 0.1-0.3% of the total mass of the main material without silica fume; The water reducer is a polycarboxylate water reducer, and its dosage is 0.05-0.15% of the total mass of the main material without silica fume; The non-aluminum-sticking additive is a two-component composite additive of BaSO4 and CA6, and its dosage is 3-7% of the total mass of the main material without silica ash; The mass ratio of BaSO4 to CA6 in the non-stick aluminum additive is 2-4:1-3.
2. The silicon ash-free aluminum melting furnace lining castable according to claim 1, characterized in that: The mass ratio of BaSO4 to CA6 in the non-stick aluminum additive is 3:
2.
3. The silicon ash-free aluminum melting furnace lining castable according to claim 1, characterized in that: The polycarboxylate water reducer includes unmodified SD-water reducer and silane-modified SD-water reducer. The silane modifier used in the silane-modified SD-water reducer is γ-(methacryloyloxy)trimethoxysilane, γ-glycidyloxypropyltrimethoxysilane or γ-methacryloyloxypropyltrimethoxysilane.
4. The silicon ash-free aluminum melting furnace lining castable according to claim 3 is characterized in that: The preparation method of the silane-modified SD-water reducer is as follows: using ammonium persulfate as an initiator and mercaptopropionic acid as a chain transfer agent, acrylic acid, isoprenyl polyoxyethylene ether and a silane modifier are mixed in a mass ratio of 1:1:1, copolymerized in a water bath at 80°C to obtain a copolymer, and then adjusting the pH to 7.
5. The silicon ash-free aluminum melting furnace lining castable according to claim 1, characterized in that: The melting point of the low-melting-point polypropylene fiber is 90-100° C., and the amount of the low-melting-point polypropylene fiber used is 0.2% of the total mass of the main material without silica fume.
6. The silicon ash-free aluminum melting furnace lining castable according to claim 1, characterized in that: In the main material without silica fume, the particle size of the plate-shaped corundum powder is 0.001-3 mm, the particle size of the white corundum powder is 3-10 mm, the particle size of the alumina powder is less than 0.045 mm, and the binder is 70 calcium aluminate refractory cement.
7. A method for preparing a silicon ash-free aluminum melting furnace lining, characterized in that: The method is prepared by using the casting material according to any one of claims 1 to 6; the method specifically comprises the following steps: 1) Casting material preparation: Weigh the components of the casting material according to the above mass percentages, first mix the plate-shaped corundum powder, white corundum powder, binder, alumina powder, water reducer and non-stick aluminum additive, then add an appropriate amount of water to adjust the material to have appropriate fluidity, then add the fiber material and continue stirring to obtain the casting material; 2) Casting material construction: The prepared casting material is poured into the prefabricated mold in the aluminum melting furnace through the casting equipment while being stirred, in preparation for drying and curing; 3) Drying and curing: After the construction of the castable is completed, the castable injected into the mold is baked to dissipate the moisture inside until it is completely dry; 4) Demolding: After the castable in the mold is completely dry, remove the mold to obtain the aluminum melting furnace lining.
8. The method for preparing the lining of a silicon ash-free aluminum melting furnace according to claim 7, characterized in that: In step 1), the casting material is prepared: after adding the fiber material, the initial stirring speed is 20-100 rpm, stirring for 5-10 minutes to gradually disperse the fibers; then the stirring speed is gradually increased to 100-300 rpm, stirring for 10-15 minutes, until the casting material reaches the required uniformity and fluidity; finally, the stirring speed is maintained at 200-300 rpm to ensure that the fibers do not clump and are evenly dispersed; and the stirring direction remains unchanged after adding the fiber material.
9. The method for preparing the lining of a silicon ash-free aluminum melting furnace according to claim 7, characterized in that: In step 3), the drying and curing process is as follows: Heating: First, heat to 90℃ at a rate of 2℃ / min and keep warm for 30min; then heat to 95℃ at a rate of 1℃ / min and keep warm for 3h; then heat to 99℃ at a rate of 0.5℃ / min and keep warm for 2h; Cooling: Then cool to 95℃ at a rate of 0.5℃ / min and keep warm for 30min; then cool to 90℃ at a rate of 1℃ / min and keep warm for 2h; finally cool to room temperature at a rate of 3℃ / min and demould.
Citation Information
Patent Citations
Impervious castable for aluminum melting furnace and preparation method
CN109400188A
A kind of non-stick aluminum casting material and preparation method thereof
CN117383912B
Calcium hexaluminate based pouring material not polluting high-purity aluminum solution
CN102211945A
Manufacturing method of energy-saving aluminum water flow tank prefabricated member
CN109400145A